1975
DOI: 10.1136/thx.30.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breath holding in hypercapnia as a simple clinical test of respiratory chemosensitivity.

Abstract: N. S. (1975). Thorax, 30,[337][338][339][340][341][342][343] Evaluation of breath holding in hypercapnia as a simple clinical test of respiratory chemosensitivity. Breath holding was used as the basis of a simple test of respiratory chemosensitivity. Breath holding was begun at selected degrees of hypercapnia produced by CO2 rebreathing. In 16 healthy control subjects there was a linear regression of the log of breath-holding time on the Pco2 at the start of breath holding. Breath-holding time (BHT) and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Several adaptations in CO 2 sensitivity have been reported in divers [11,18,20,22,23], but non-chemical factor modifications have not been demonstrated to date. The aim of this study was to dissociate chemical and non-chemical stimuli and to evaluate non-chemical factor adaptations in divers and non-divers by assessing the modifications in respiratory centre activity in response to hypercapnic stimuli and for different BHT.…”
Section: Introductionmentioning
confidence: 91%
“…Several adaptations in CO 2 sensitivity have been reported in divers [11,18,20,22,23], but non-chemical factor modifications have not been demonstrated to date. The aim of this study was to dissociate chemical and non-chemical stimuli and to evaluate non-chemical factor adaptations in divers and non-divers by assessing the modifications in respiratory centre activity in response to hypercapnic stimuli and for different BHT.…”
Section: Introductionmentioning
confidence: 91%
“…Previously, investigators have demonstrated that chemoreflex sensitivity (a key determinant of loop gain) during wakefulness – measured via CO 2 rebreathing (Stanley et al . ) or dynamic CO 2 administration (Trembach & Zabolotskikh, ) – can be estimated simply by measuring how long participants can voluntarily hold their breath for (“maximal breath‐hold duration”). Conceptually, during a breath‐hold, participants generate their own hypoxia–hypercapnia at a rate determined by the plant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The suprapontine origin of this phenomenon, generally referred to as "wakefulness drive to breathe," is confirmed by its disappearance in patients with forebrain lesions (44). Conversely, when the drive to breathe is increased to meet the metabolic needs of the body, it can become increasingly difficult for suprapontine ventilatory commands to override the automatic ones (6,52,62), even though hypercapnia facilitates the response of the diaphragm to corticospinal inputs (64). How cortical and subcortical commands interfere thus depends on the prevailing CO 2 levels (44,58,64).…”
mentioning
confidence: 97%